2022
DOI: 10.1080/13621718.2022.2095195
|View full text |Cite
|
Sign up to set email alerts
|

Transient liquid phase bonding of graphite to Ti6Al4V alloy

Abstract: Transient liquid phase bonding of graphite to Ti6Al4V alloy has been conducted with Cu foil, Ti/Cu and Cu/Ti/Cu foils, respectively. A diffusion zone containing Ti-based solid solution and Ti 2 Cu develops between the bonding zone and Ti6Al4V substrate for all the joints. The bonding zones of joints with Cu foil and Cu/Ti/Cu foils are both composed of TiCu and Ti 2 Cu. However, the bonding zone of joint with Ti/Cu foils consists of zones I, II and III. Both zones I and III are mainly comprised of TiCu and Ti 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The thickness of the joining region (80–85 µm) is lower than those of Ti/Cu foils (100 µm), which may be caused by the liquid filler infiltration into the graphite and spillage of the eutectic liquid phase as well as the consumption of interfacial reaction between the graphite and the Ti-Cu liquid filler. Jiang et al [7] also reported the thickness decrease of the joining region in graphite/Ti6Al4V bonding with Cu/Ti foils, which was caused by the infiltration of Cu-Ti eutectic liquid phase into the graphite.
Figure 1 Micrograph (a) and EDX elemental distributions (b–e) of the graphite/Mo joint using Ti/Cu foils.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness of the joining region (80–85 µm) is lower than those of Ti/Cu foils (100 µm), which may be caused by the liquid filler infiltration into the graphite and spillage of the eutectic liquid phase as well as the consumption of interfacial reaction between the graphite and the Ti-Cu liquid filler. Jiang et al [7] also reported the thickness decrease of the joining region in graphite/Ti6Al4V bonding with Cu/Ti foils, which was caused by the infiltration of Cu-Ti eutectic liquid phase into the graphite.
Figure 1 Micrograph (a) and EDX elemental distributions (b–e) of the graphite/Mo joint using Ti/Cu foils.
…”
Section: Resultsmentioning
confidence: 99%
“…The result showed that the Ni foil introduction could alleviate the joint stress, thus contributing to the promotion of the joint strength. Jiang et al [7] introduced metal foils including Cu, Cu/Ti and Cu/Ti/Cu foils in graphite/Ti6Al4V alloy TLPB. The joint with Cu/Ti/Cu foils showed the most satisfactory interfacial bonding, thus exhibiting the highest shear strength.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, graphite/Cu brazing was also achieved with Cu-TiH2 based fillers [5,6]. Furthermore, transient liquid phase bonding (TLPB), based on formation of liquid phase by the eutectic reaction between metal foils or between metal foil and metal substrate, is an alternative technique for joining dissimilar materials [7]. Ti metal foil has been used to create a good bond between graphite and Cu by TLPB due to the formation of a eutectic phase between the Ti foil and Cu substrate [8].…”
Section: Introductionmentioning
confidence: 99%